RESPON PASANGAN USIA SUBUR (PUS) TERHADAP PROGRAM KELUARGA BERENCANA (KB) DI DESA TANJUNG BELIT KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Siti Muthiah; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The research aims is to determine how the response of fertile couples to family planning programs and find out what affects the response of fertile couples to family planning in the village of Tanjung Belit Siak Kecil District Bengkalis.The population is fertile couples who have 2 children, as many as 234 couples in the village of Tanjung Belit Siak Kecil Bengkalis. Of all respondents, amounting to 234 couples, 140 couples of whom are not participating in family planning program while 95 couples are the participant. Due to limitations of the research so we decided a representative sample of the population by 43 % in order to obtain 60 respondents that not planning acceptors and 40 respondents that planning acceptors. Data analysis using quantitative descriptive.The study states that the factors affecting the respondents for not participating family planning is because of their have a low level of education, their jobs are largely farmers and a couple aged 36 to 40 years old is the age that is no longer fertile. In the village of Tanjung Belit, parental education level is affect the number of children they have. Respondents did not all know about the family planning program, there were 33 respondents or 55 % of all existing subjects admitted that they were aware of any family planning program in the village of Tanjung Belit. While 27 respondents or 45 % of all subjects who claimed not to know that there is no family planning program in their village. The most dominant factor that affecting the response to the couples is the education of respondents.